Teaching work and relationships with students from the perspective of pre-service teachers' representations - Sánchez Sánchez, Gerardo Ignacio (2017)
The current situation of Postmodernity raises the challenge, to initial teacher training, to ensure a proper inclusion to school contexts which are highly stressed regarding training demands. This research explores the representations pre-service teachers have regarding teaching and their relationship with elementary school children. Using a qualitative methodological approach, with an exploratory-descriptive scope, starting from the use of interviews, the present piece of research was built in a dialogue arena with 50 students from the Elementary Teacher Education Program, with a minor in Spanish Language, Mathematics, Social and Natural Science of Universidad Católica del Maule. The results show the teaching work representation as a human effort equipped with a complexity derived from the requirement of integrality and otherness, and from the demands of a diverse, technological society. It can be concluded that while becoming integrated into the classroom, pre-service teachers are confronted with an area defined as complex and uncertain, in which it is important to consider that they are active and heterogeneous with respect to their willingness, interests, and capacity to learn, and as a consequence these factors stress the relationship and the teacher authority status. From the point of view of implications for initial teacher training, pre-service practitioners fail to see that the same rationality with which the school operates roughly explains the complexity of the new territory where they will have to carry out their work.